2021
DOI: 10.1186/s12903-021-01928-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender and age group modified association of dental health indicators with total occlusal force among Korean elders

Abstract: Background This study aimed to investigate the distribution of objective total occlusal force (TOF) and its association with dental health indicators: dental status, number of natural teeth (NT), natural and rehabilitated teeth, natural posterior teeth (NT-Post), and natural and rehabilitated posterior teeth among Korean elders after controlling for various confounders encompassing socio-demographic factors, behavioral factors and health/oral health factors. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The present results showed a signifi cant diff erence in occlusal force between before and after cleaning. The rate of reduction in occlusal force was 24.6% for Group M with manual cleaning, which is consistent with previous reports of a reduction rate of 25.9% [10] and 21-26% [8] in occlusal force due to manual cleaning of the Dental Prescale II. These indicate that a cleaning process is needed when Dental Prescale II is used.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present results showed a signifi cant diff erence in occlusal force between before and after cleaning. The rate of reduction in occlusal force was 24.6% for Group M with manual cleaning, which is consistent with previous reports of a reduction rate of 25.9% [10] and 21-26% [8] in occlusal force due to manual cleaning of the Dental Prescale II. These indicate that a cleaning process is needed when Dental Prescale II is used.…”
Section: Discussionsupporting
confidence: 91%
“…As ways of measuring occlusal force, methods using a strain gauge transducer, piezoresistive transducer, pressure transducer, or pressure-sensitive film have been reported. Among these, the method using a dental prescale, which is a pressure-sensitive film, is widely used for young adults, the elderly, orthodontic patients, removable denture wearers, and implant denture wearers [1,[4][5][6][7][8][9]. Occlusal force has been reported to be significantly reduced with tooth loss, but significantly increased with dental treatment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Shinogaya et al (2001) reported a lower occlusal force and higher contact area between teeth in senior subjects compared to younger subjects [ 208 ]. Recent studies also present results in accordance [ 209 , 210 , 211 , 212 ]. Mechanical properties are also affected by the age of the specimen.…”
Section: Patient Dependent Factorssupporting
confidence: 78%
“…Shinogaya et al (2001) reported a higher MBF and occlusal contact area in males than in females [ 208 ]. Recent studies also present results indicating that MBF is greater in adult and elder males than females [ 209 , 210 , 212 , 216 ].…”
Section: Patient Dependent Factorsmentioning
confidence: 91%
See 1 more Smart Citation